Thanks, grandparents! (Journal of Parents and Teachers, 2016)
The following article deals with the figure of grandparents. These people who take care and protect to their children and grandchildren, also they are in charge of teaching them, their own life’s knowledge. In addition, it talks about the respect, admiration and tolerance to the elder people and the suggested activities to grandparents that they do with their grandchildren.
Keywords: education; grandparents; care; protection; knowledge; respect; admiration; tolerance; grandchildren.